EFFLORESCENCE OF ARABIC LITERATURE IN NIGERIA: APPRAISAL OF THE CONTRIBUTIONS OF SHAYKH DAWOOD TIJANI - Mikail Adebisi Folorunsho; Kamorudeen Kehinde Busari (Journal of Arabic Literature (JaLi), 2025)
It is impossible to pigeonhole the reputable Shaykh Dawood Tijani into a particular role or to compartmentalize his activities or intellectual contributions to a particular geographical region. The influence of the Shaykh in the promotion of Arabic and Islamic scholarship in Nigeria is enormous. In fact, one can hardly discuss these fields in Nigeria today without reference to the learned scholar. For the purpose of this study, however, we shall be constrained to restrict our focus to his invaluable contributions to Arabic scholarship in Nigeria, through his writings A prolific writer and sound scholar, Shaykh Dawood Tijani contributed significantly to Arabic literature with well-written books, articles and manuscripts in Arabic, on Arabic language, literature, Islam and related subjects. This study employed both historical and contextual methods, which attempt to reconstruct the significant events of the past through analysis, synthesis and verification, in assessing his intellectual background as well as the concise contents of his writings. It discovered his works as significant contributions to Arabo-Islamic literary productions. The study is expected to serve as a useful material for the literary historians and critics in documenting the Arabic literary activities in Nigeria